"Chasing my supervisor all day long like a hungry child seeking her mother!": Students' perceptions of supervisory feedback. (September 2021) - Neupane Bastola, Madhu; Hu, Guangwei
Highlights: Master's students were unsatisfied with the supervisory feedback that they received. They faced challenges related to themselves, their supervisors, and material resources. They reported emotional/cognitive/behavioural engagement with supervisory feedback. Their feedback perceptions were related to their disciplinary background. Perceptions of various aspects of feedback were related to self-reported engagement. Abstract: Students' perceptions of supervisory feedback can have a profound impact on their engagement with and agency in learning. Understanding students' perceptions is vital to tailoring feedback to their needs. However, little is known about student perceptions of supervisory feedback on master's theses. To address this lacuna, the present study collected feedback perceptions with a written questionnaire from 434 students in four disciplines (English Education, English Studies, Physics, and Engineering) at a Nepalese university. Quantitative and qualitative analyses revealed that the students as a group did not receive sufficient supervisory support and found their supervisors' feedback practices unsatisfactory. Despite the inadequate support, they reported emotional, cognitive, and behavioural engagement with the supervisory feedback that they received, and their perceptions of supervisory feedback significantly predicted their self-reported engagement. Furthermore, perceptions of supervisory feedback and self-reported engagement varied significantly across the disciplines. Implications are derived from these findings for improving supervisory feedback practices.